PARTISIPASI TENAGA KERJA, MODAL MANUSIA, PENGELUARAN PEMERINTAH UNTUK PENDIDIKAN DAN PERTUMBUHAN EKONOMI: ANALISIS PADA NEGARA-NEGARA G20 - Krisna, Puguh Samudra Aji; Nurul Badriyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this research is to analyze the impacts of the determinants of work force participation rate, human capital, government expenditure on education on the economic growth of G20 countries. The cross-sectional data of nineteen G20 countries during the analysis period of 2015-2021 was analyzed using panel data regression. This study finds that work force participation rate positively and significantly influences economic growth and that human capital also can enhance economic growth although insignificantly, However, government expenditure on education has positive and significant results on economic growth. These findings contribute to literatures that discuss factors affecting economic growth at the global level. They can also be used as considerations for promoting policies that reduce participation obstacles, such as discrimination, education disparity, and socioeconomic factors. The member countries of G20 can implement policies that support equal access for employment, relevant skill development, and inclusive policies for marginal and vulnerable groups.